KCTD5 and Ubiquitin Proteasome Signaling Are Required for Helicobacter pylori Adherence - Álvarez, Alhejandra; Uribe, Felipe; Canales, Jimena; Romero, Cristóbal; Soza, Andrea; Peña, María A.; Antonelli, Marcelo; Almarza, Oscar; Cerda, Oscar; Toledo, Héctor (Frontiers in Cellular and Infection Microbiology, 2017)
In order to establish infection, bacterial pathogens modulate host cellular processes by using virulence factors, which are delivered from the bacteria to the host cell leading to cellular reprogramming. In this context, several pathogens regulate the ubiquitin proteasome system in order to regulate the cellular effectors required for their successful colonization and persistance. In this study, we investigated how Helicobacter pylori affect the ubiquitination of the host proteins to achieve the adherence to the cells, using AGS gastric epithelial cells cultured with H. pylori strains, H. pylori 26695 and two isogenic mutants H. pylori cag::cat and vacA::apha3, to characterize the ability of H. pylori to reprogram the ubiquitin proteasome systems. The infection assays suggest that the ubiquitination of the total proteins does not change when cells were co-culture with H. pylori. We also found that the proteasome activity is necessary for H. pylori adhesion to AGS cells and the adherence increases when the level of KCTD5, an adaptor of Cullin-3, decrease. Moreover, we found that KCTD5 is ubiquitinated and degraded by the proteasome system and that CagA and VacA played no role on reducing KCTD5 levels. Furthermore, H. pylori impaired KCTD5 ubiquitination and did not increase global proteasome function. These results suggest that H. pylori affect the ubiquitin-proteasome system to facilitate the adhesion of this microorganism to establish stable colonization in the gastric epithelium and improve our understanding of how H. pylori hijack host systems to establish the adherence.